The Digital Assessment of Learning: Current Situation and Perspectives: Case of Teachers of Life and Earth Sciences - Mohammed Rehhali; Abderrazzak Mazouak; Said Belaaouad (Journal of Information Technology Management)
The constant evolution of technological tools and the benefit of the introduction of new technologies in the teaching and learning process in schools, suggests that the possibilities of using digital technology in the practices of the evaluation of learning inside and outside the classroom.Faced with the diversity of technical tools and methods, the teacher is called upon, before addressing his learners, to make a certain number of technical, didactic and pedagogical choices, to set his pedagogical scenario, this is all the more so. Necessary for the conduct of learning activities or to design and implement its assessment tool. In this perspective, we are entitled to ask the question relating to the attitudes and feedbacks of teachers and learners regarding the integration of ICT in assessment practices. This question is broken down into several sub-questions: "At what points, and how do teachers of Life and Earth Sciences integrate digital technology into their assessment practices?" is this integration determined by the educational pathways? What interest and what limit of the use of digital technology according to teachers and learners? " To answer our problem, we opted for export research, the recommended methodology of which is based on a multidimensional survey, in which we first questioned the teachers around the use of new technologies in the evaluation process, and secondly, to identify the degree of motivation and commitment of learners in instrumented and innovative assessment situations.Our research context is represented by 34 schools, 22 from qualifying secondary education and 12 from college education (from the provincial delegation of Taza), with a varied population of 431 students of all levels and sectors, as well as than a number of 132 teachers of life and earth sciences.Finally, confirming that despite the satisfaction of the majority of teachers and students with respect to the functional qualities and the contribution of technological tools in evaluation practices, some disparities were noted whether at the technical, spatiotemporal level or even organizational.